Arabische Dialektgeographie : eine Einführung - Behnstedt, P. (Handbook of Oriental Studies. Section 1 The Near and Middle East, 2005)
This volume is the first comprehensive and systematic description of the dialect geography of the Arabic language which investigates the methods and insights developed in the European context and how these can be applied to the domain of Arabic. It also deals briefly with the problems of the historical development of the modern Arabic dialects. With the help of 112 maps it examines topics such as types of maps, interpretation of maps, areal norms and their significance for Arabic and defining dialect borders. For the first time dialectometrical procedures are applied to Arabic dialects. It can be used as a practical introduction into Arabic dialect geography because in addition it discusses extensively methods of designing dialect geography maps a investigational techniques in the field.